Enhancing customer loyalty at Naza Talyya Melaka / Siti Suraya Fareha Mohd Taupet - Mohd Taupet, Siti Suraya Fareha (2014)
Customer loyalty is important in any business. For hotel industry, it will imply higher market share and ability to demand relatively higher prices. Besides, it ensures the future income to the hotel. The customer perceptions are the elements that used in evaluating the customer loyalty towards the organization. This study focused in perception on customer in term of hotel image, physical quality, staff service and value for money. All this elements used as an independent variable and dependent variables is customer loyalty. The main objective of this research is to identify the level of customer loyalty towards Naza Talyya Melaka. Second is to identify the relationship between customer perceptions and customer loyalty. Third is to identify the most influential factor toward customer loyalty at Naza Talyya Melaka. This research is conducted at Naza Talyya Melaka and 65 respondents have been asked randomly using questionnaire to gain feedback to the hotel.